Silver-induced layer exchange and crystallization of a-Si films investigated using in situ scanning transmission electron microscopy - Yadav, Surbhi; Birajdar, B. I.; Kraschewski, Simon; Apeleo Zubiri, Benjamin; Antesberger, T.; Stutzmann, M.; Spiecker, Erdmann (Journal of Applied Physics, 2024)
Ag-induced crystallization and layer exchange (AgILE) in a stack of amorphous Si/Ag/quartz substrate has been investigated using optical microscopy, scanning electron microscopy, transmission electron microscopy (TEM), scanning TEM-high angle annular dark field (STEM-HAADF) imaging, and electron tomography, covering length scales from a few tens of micrometers to a few tens of nanometers. The size of Ag grains in the underlying as-deposited Ag film varied from ∼10 to 500 nm. The following processes could be discerned using in situ heating of plan-view samples at 500 °C in STEM: (i) AgILE propagation preferentially along regions of small Ag grains, (ii) formation of pushed-up Ag in the vicinity of AgILE reaction cells, (iii) migration and agglomeration of pushed-up Ag on small and large Ag grains, which tend to inhibit AgILE and promote dendricity, and (iv) dispersion of pushed-up Ag, which tend to reduce dendricity. The resulting dendricity was largely confined to the peripheral regions of the impinging reaction cells and decreased with annealing time. In contrast, dendricity due to AgILE and crystallization at 550 °C is stable and extends right from the center to the periphery of the reaction cells. The microscopic mechanism of AgILE and, in particular, the effect of annealing temperature is investigated. The results are discussed in the light of existing literature and compared with Al-induced layer exchange. Annealing at temperature equal to or slightly less than 500 °C is found to be necessary in the case of AgILE to avoid dendricity and to obtain a continuous Si layer with large Si grains.
CRIS-Team Scopus Importer:2024-09-13